Ethylene Signaling Modulates Cortical Microtubule Reassembly in Response to Salt Stress. Issue 3 (5th February 2018) - Dou, Liru; He, KaiKai; Higaki, Takumi; Wang, Xiangfeng; Mao, Tonglin
Abstract : The plant hormone ethylene and its associated signaling pathway are involved in cortical microtubule reassembly, a process that is critical for the salt stress response in Arabidopsis. Abstract: Regulation of cortical microtubule reorganization is essential for plant cell survival under high salinity conditions. In response to salt stress, microtubules undergo rapid depolymerization followed by reassembly to form a new microtubule network that promotes cell survival; however, the upstream regulatory mechanisms for this recovery response are largely unknown. In this study, we demonstrate that ethylene signaling facilitates salt stress-induced reassembly of cortical microtubules in Arabidopsis ( Arabidopsis thaliana ). Microtubule depolymerization was not affected under salt stress following the suppression of ethylene signaling with Ag + or in ethylene-insensitive mutants, whereas microtubule reassembly was significantly inhibited. ETHYLENE-INSENSITIVE3, a key transcription factor in the ethylene signaling pathway, was shown to play a central role in microtubule reassembly under salt stress. In addition, we performed functional characterization of the microtubule-stabilizing protein WAVE-DAMPENED2-LIKE5 (WDL5), which was found to promote ethylene-associated microtubule reassembly and plant salt stress tolerance. These findings indicate that ethylene signaling regulates microtubule reassembly by up-regulating WDL5 expression in response to salt stress, thereby implicating ethylene signaling in salt-stress tolerance in plants.